Peran Kecerdasan Buatan dalam Model Kematangan Digital: Analisis Bibliometrik (2015-2024) - Agi Fahrisky; Achmad Nurmandi; Muhammad Younus; Herman Lawelai (Society, 2025)
This study investigates the role of Artificial Intelligence (AI) in advancing Digital Maturity Models (DMMs) to support digital transformation across various sectors. Although AI technologies have been widely adopted, few studies have explicitly examined how AI influences the dimensions of digital maturity or mapped the evolving research landscape on this subject. To address this gap, a bibliometric analysis was conducted using 430 journal articles published between 2015 and 2024, sourced from the Scopus database. Quantitative methods were employed using R Studio and the Bibliometrix package to analyze publication trends, keyword co-occurrences, and international research collaborations. The findings reveal a notable increase in AI-related DMM publications since 2022, with key themes including technological innovation, strategic transformation, and socio-organizational adaptation. This study contributes to the existing body of knowledge by offering a systematic overview of research developments, highlighting critical gaps, and laying the groundwork for adaptive AI maturity models. Its novelty lies in applying bibliometric techniques to uncover thematic structures that can inform future research agendas and policy directions in digital transformation.